Something beyond paycheque to boosting employee retention: evidence from a South Indian hospital - M. Bharath (Vilakshan (XIMB Journal of Management))
Purpose – This paper aims to emphasize the need for a strategic approach to employee retention beyond financial benefits. This is directly proportional to employee retention. Bringing out the retention measures preferred by employees, depicting the relationship of demographic profile with employee retention tendency and exploring implications giving importance to beyond paycheque factors are the objectives of the study. Design/methodology/approach – This study uses applied qualitative approach with a realistic view to collect the details of retention measures and practices from purposively selected 36 health-care experts by the conduct of interview using a one-to-one discussion with written notes. With quantitative approach, opinion survey was administered to receive the perceived opinion of randomly selected 350 health-care employees on paycheque and on beyond paycheque factors boosting their intention to stay. Bhattacharya and Ramachandran’s health-care study framework on retention was applied for the identification of the factors. Findings – Both paycheque and beyond paycheque benefits are important for retention. Most respondents prefer beyond paycheque factors practiced at sampled hospital. Age, marital status and residence of employees are significantly associated with retention. The strategic initiatives of the sampled hospital to retention concerning motivational needs of employees in the workplace are thank you board, camp head, ad act camp, success corner and so forth. Research limitations/implications – Addressing health-care work and relationship-related issues in terms of employee retention giving importance to beyond paycheque benefits – remedy for compassion fatigue health-care employees face in routine works, meeting promises made by management regarding paycheque or beyond paycheque benefits, employees participative in decisions in medical, clinical and in functional areas, reducing workload and role stress by the conduct of role analysis. Originality/value – Many research studies are emphasizing the contribution of financial benefits to employee retention. Only a few studies have been carried out exploring and emphasizing the importance of beyond financial benefits motivating employee retention. This is the study of evidence from a hospital that gives strategic importance to beyond paycheque elements as well as paycheque elements.